A Propensity Score-Matched Cohort Analysis of Outcomes After Stereotactic Radiosurgery in Older versus Younger Patients with Dural Arteriovenous Fistula: An International Multicenter Study - Mohammed, Nasser; Hung, Yi-Chieh; Xu, Zhiyuan; Starke, Robert M; Kano, Hideyuki; Lee, John; Mathieu, David; Kaufmann, Anthony M; Grills, Inga S; Cifarelli, Christopher P; Vargo, John A; Chytka, Tomas; et al. (World neurosurgery, 2019)
OBJECTIVE: This study aims to evaluate the outcomes of Gamma Knife stereotactic radiosurgery (SRS) for dural arteriovenous fistulas (dAVFs) in older patients (≥65 years) compared with younger patients (age <65 years). METHODS: Two groups with a total of 96 patients were selected from a database of 133 patients with dAVF from 9 international medical centers with a minimum 6 months follow-up. A 1:2 propensity matching was performed by nearest-neighbor matching criteria based on sex, Borden grade, maximum radiation dose given, and location. The older cohort consisted of 32 patients and the younger cohort consisted of 64 patients. The mean overall follow-up in the combined cohort was 42.4 months (range, 6-210 months). RESULTS: In the older cohort, a transverse sinus location was found to significantly predict dAVF obliteration (P = 0.01). The post-SRS actuarial 3-year and 5-year obliteration rates were 47.7% and 78%, respectively. There were no cases of post-SRS hemorrhage. In the younger cohort, the cavernous sinus location was found to significantly predict obliteration (P = 0.005). The 3-year and 5-year actuarial obliteration rates were 56% and 70%, respectively. Five patients (7.8%) hemorrhaged after SRS. Margin dose ≥25 Gy was predictive of unfavorable outcome. The obliteration rate (P = 0.3), post-SRS hemorrhage rate (P = 0.16), and persistent symptoms after SRS (P = 0.83) were not statistically different between the 2 groups. CONCLUSIONS: SRS achieves obliteration in most older patients with dAVF, with an acceptable rate of complication. There was no increased risk of postradiosurgery complications in the older cohort compared with the younger patients.
Keywords: cévní malformace centrálního nervového systému; Cavernous Sinus; sinus transversus; Humans; Transverse Sinuses; lidé středního věku; dítě; Older; kohortové studie; Child; Arteriovenous; Female; Aged; mladý dospělý; dospělí; tendenční skóre; věkové faktory; Gamma Knife; výsledek terapie; senioři; lidé; Dural; Stereotactic radiosurgery; Cohort Studies; sinus cavernosus; radiochirurgie; Adult; Radiosurgery; Fistula; ženské pohlaví; Kaplanův-Meierův odhad; Male; Middle Aged; Adolescent; Treatment Outcome; Aged, 80 and over; Young Adult; senioři nad 80 let; Kaplan-Meier Estimate; Age Factors; Central Nervous System Vascular Malformations; mužské pohlaví; mladiství; Propensity Score